2000
DOI: 10.1093/bja/85.2.305
|View full text |Cite
|
Sign up to set email alerts
|

Which is most pungent: isoflurane, sevoflurane or desflurane?

Abstract: We compared the pungency and tolerability of three inhaled anaesthetics in a randomized, double-blind study. Eighty-one unpremedicated patients (n = 27, each group) inhaled 2 MAC of isoflurane (2.3%), desflurane (12%) or sevoflurane (4%) for 60 s from an anaesthetic breathing circuit via a mask. Two blinded observers recorded coughing, complaints of burning and irritation, and how long the inhalation was tolerated. One sevoflurane patient coughed, but completed the study period, whereas 11 isoflurane patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 7 publications
(2 reference statements)
1
76
0
3
Order By: Relevance
“…The order of the four anaesthetics in terms of their irritancy (sevoflurane < halothane < isoflurane < desflurane) confirms the results of previous studies [19][20][21]. The similarity of the irritancy of halothane and isoflurane was surprising, but a large fraction of the incidence of adverse airway events to halothane came from one volunteer (Tables 3 and 4).…”
supporting
confidence: 84%
“…The order of the four anaesthetics in terms of their irritancy (sevoflurane < halothane < isoflurane < desflurane) confirms the results of previous studies [19][20][21]. The similarity of the irritancy of halothane and isoflurane was surprising, but a large fraction of the incidence of adverse airway events to halothane came from one volunteer (Tables 3 and 4).…”
supporting
confidence: 84%
“…Moreover, VGAs appear to activate exclusively capsaicin-sensitive or TRPV11 sensory neurons (Mutoh et al, 1998). Indeed, volatile anesthetics such as isoflurane and desflurane are perceived as pungent and cause airway irritation when inhaled, which has limited their use as induction agents (Eger, 1995;TerRiet et al, 2000). Following up on these findings showed that these VGAs directly activate TRPA1 and sensitize TRPV1 Matta et al, 2008;Eilers et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to isoflurane, a high concentration of sevoflurane did not alter HR but caused MAP to decrease, probably because of its direct effect on vascular smooth muscle. Because sevoflurane is less pungent than isoflurane, 18 differences in the hemodynamic variables between isoflurane and sevoflurane might have resulted from their different potentials to elicit airway irritation. This finding corresponds to the results of Tanaka et al 8 showing that a stepwise increase in isoflurane concentration from 0.9 MAC to 2.7 MAC elicited tachycardia and hypertension but that sevoflurane did not induce hyperdynamic responses.…”
mentioning
confidence: 99%